A mobile phone frame based on titanium-aluminum composite material and its processing technology
Through wire profile rolling composite technology and multi-step processing technology, titanium-aluminum composite materials with high interface bonding strength and mechanical properties were prepared, which solved the processing problems of layered Al/Ti metal composite materials in the prior art during the cutting process, and achieved high-performance production of mobile phone frames.
Patent Information
- Application Number
- CN202410339069.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-03-25
AI Technical Summary
The existing layered Al/Ti metal composite materials are prone to processing problems such as curling edge layering and cracking during the cutting process, resulting in high residual rate, low production efficiency and high cost of mobile phone frame products.
Titanium-aluminum composite materials are prepared by wire profile rolling composite technology. Through wire surface cleaning treatment, lactation treatment, hetero-temperature heating treatment, asynchronous rolling composite, double-sided edge grinding, cutting edge wrapping, straightening and shaping, solid solution treatment, aging treatment and multi-point constant speed straightening treatment, the interface bond strength and mechanical properties of titanium-aluminum composite materials are improved.
The high interface bonding strength and mechanical properties of titanium-aluminum composite materials are achieved, which avoids the problems of edge-beaming and cracking during the cutting process, reduces the product residual rate and production cost, and improves production efficiency.
Smart Images

Figure CN118204721B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of mobile smart terminal accessory processing technology, and in particular to a mobile phone frame based on titanium-aluminum composite material and its processing technology. Background Technology
[0002] Currently, the preparation technology of layered metal composite materials mainly focuses on composite sheet preparation technology. With the development and maturity of the technology, literature reports on the production of layered metal composite materials by rolling strip profiles have gradually emerged. However, both sheet profile rolling composite technology and strip profile rolling composite technology involve strips with a large width and thickness ratio; there are currently no reports on wire rod rolling composite technology with a smaller width and thickness ratio. Regarding the existing sheet profile rolling composite technology and strip profile rolling composite technology, both still have the following problems: poor interfacial composite strength, poor thickness uniformity, high internal stress at the composite interface, and low yield. Due to the high internal stress at the composite interface of layered metal composite materials, processing problems such as edge warping, delamination, and cracking often occur when cutting the product into small pieces. When used in subsequent product applications, the product defect rate is high, production efficiency is low, and production costs are high.
[0003] As the most common mobile smart terminal device, mobile phones are increasingly using layered titanium-aluminum metal composite materials to fabricate high-performance phone frames. However, existing technologies for preparing layered Al / Ti metal composite materials, using either plate-shaped or strip-shaped profile rolling composite technology, require cutting into smaller wires for processing. During this cutting process, the applicant encountered problems such as edge warping, delamination, and cracking, resulting in a high defect rate, low production efficiency, and high production costs for phone frames, thus hindering the development and widespread adoption of high-performance phone frames. Therefore, the applicant provides a titanium-aluminum composite material prepared using a wire-profile rolling composite technology suitable for mobile phone frame manufacturing. Summary of the Invention
[0004] To address the technical problems existing in the prior art, this application provides a mobile phone frame based on titanium-aluminum composite material and its processing technology.
[0005] The mobile phone frame based on titanium-aluminum composite material provided in this application is achieved through the following technical solution:
[0006] A mobile phone frame based on titanium-aluminum composite material includes a titanium-aluminum composite material. The titanium-aluminum composite material is made from titanium wire and aluminum alloy wire through a process involving wire surface cleaning, wire surface roughening, differential heating, asynchronous rolling, double-sided edge grinding, edge cutting, straightening and shaping, solution treatment, aging treatment, and multi-point constant-speed straightening. The titanium wire in the titanium-aluminum composite material is pure titanium wire or titanium alloy wire. The aluminum alloy wire in the titanium-aluminum composite material is Al-Si-Mg alloy wire or interface-modified Al-Si-Mg alloy wire. The interface-modified Al-Si-Mg alloy wire contains 0.2-2 wt% nano-scale interface modifier, with the balance being Al-Si-Mg alloy. The interfacial bonding strength of the titanium-aluminum composite material is 180-220 MPa, the elongation is 18-20%, and the hardness of the aluminum alloy in the titanium-aluminum composite material is 118-128 HV.
[0007] This application combines specific processing techniques with wire matching technology to produce a titanium-aluminum composite material with high interfacial bonding strength that does not delaminate when bent. The prepared titanium-aluminum composite material has an interfacial bonding strength of 180-220MPa, an elongation of 18-20%, and an aluminum alloy hardness of 118-128HV.
[0008] Preferably, when the aluminum alloy wire in the titanium-aluminum composite material is an Al-Si-Mg alloy wire, then the Al-Si-Mg alloy wire is a 6-series aluminum alloy wire; when the aluminum alloy wire in the titanium-aluminum composite material is an interface-modified Al-Si-Mg alloy wire, then the Al-Si-Mg alloy wire in the interface-modified Al-Si-Mg alloy wire is a 6-series aluminum alloy wire.
[0009] Preferably, when the aluminum alloy wire in the titanium-aluminum composite material is an Al-Si-Mg alloy wire, the Al-Si-Mg alloy wire is one of 6061 aluminum alloy wire, 6063 aluminum alloy wire, and 6013 aluminum alloy wire; when the aluminum alloy wire in the titanium-aluminum composite material is an interface-modified Al-Si-Mg alloy wire, the Al-Si-Mg alloy wire in the interface-modified Al-Si-Mg alloy wire is one of 6061 aluminum alloy wire, 6063 aluminum alloy wire, and 6013 aluminum alloy wire.
[0010] By adopting the above technical solution, the interfacial bonding strength and mechanical properties of the prepared titanium-aluminum composite material can be guaranteed.
[0011] Preferably, the average particle size of the nanoscale interface modifier is 50-200 nm; the nanoscale interface modifier includes a carrier and an over-plated metal element fixed to the surface of the carrier in the form of single atoms via covalent bonds, wherein the over-plated metal element is Ti or Al, and the mass ratio of Ti to Al is (0.8-1.2):(0.8-1.2); the carrier is at least one of MAX phase nano-ceramic powder, graphene, and carbon nanotubes; the MAX phase nano-ceramic powder is at least one of Ti2AlN nano-ceramic powder, Ti3AlC2 nano-ceramic powder, Ti3AlCN nano-ceramic powder, Ti2AlC nano-ceramic powder, and Al-Ti3AlC2 nano-ceramic powder; the doping rate of the over-plated metal element in the nanoscale interface modifier is 5-10 wt%.
[0012] Preferably, the mass ratio of Ti to Al in the overplated metal element is 1:1; the doping rate of the overplated metal element in the nanoscale interface modifier is 8±0.5wt%; and the carrier is composed of carbon nanotubes and / or graphene combined with Al-Ti3AlC2 nano-ceramic powder.
[0013] Preferably, the aluminum alloy wire in the titanium-aluminum composite material is an interface-modified Al-Si-Mg alloy wire, wherein the Al-Si-Mg alloy wire in the interface-modified Al-Si-Mg alloy wire is 6013--T4-S-ST-1-aluminum alloy wire; the interface-modified Al-Si-Mg alloy wire contains 0.5-0.8wt% of nano-scale interface modifier, and the balance is Al-Si-Mg alloy.
[0014] By adopting the above technical solution, the interfacial bonding strength between aluminum alloy wire and titanium wire can be further improved.
[0015] Secondly, the processing technology for a mobile phone frame based on titanium-aluminum composite material provided in this application is achieved through the following technical solution:
[0016] A processing technology for a mobile phone frame based on titanium-aluminum composite material includes the following steps:
[0017] Step 1, cleaning the wire surface:
[0018] The titanium wire raw material has a rectangular cross-section; the aluminum alloy wire raw material has an isosceles trapezoidal cross-section.
[0019] Titanium wires were subjected to ultrasonic cleaning with acetone, ultrasonic cleaning with deionized water, ultrasonic cleaning with acid, ultrasonic cleaning with deionized water, and low-temperature drying under nitrogen protection to obtain surface-cleaned titanium wires.
[0020] Meanwhile, aluminum alloy wires were subjected to ultrasonic cleaning with acetone, ultrasonic cleaning with deionized water, ultrasonic cleaning with acid, ultrasonic cleaning with deionized water, and low-temperature drying under nitrogen protection to obtain aluminum alloy wires with surface cleaning treatment.
[0021] Step 2, surface roughening treatment of the wire:
[0022] The titanium wire that underwent surface cleaning in step one was subjected to laser scanning texturing, followed by ultrasonic cleaning with acid solution, ultrasonic cleaning with deionized water, and low-temperature drying under nitrogen protection to obtain the surface-textured titanium wire.
[0023] Simultaneously, the aluminum alloy wire that underwent surface cleaning in step one is subjected to laser scanning texturing, followed by ultrasonic cleaning with acid solution, ultrasonic cleaning with deionized water, and low-temperature drying under nitrogen protection to obtain the surface-textured aluminum alloy wire.
[0024] Step 3, Wire Heating Treatment: The titanium wire with surface roughening treatment in Step 2 is subjected to high-frequency heating to 300-400℃ for 100-120 seconds, followed by holding at 360-390℃ for 5-10 minutes; simultaneously, the aluminum alloy wire with surface roughening treatment in Step 2 is subjected to high-frequency heating to 400-460℃ for 160-200 seconds, followed by holding at 400-440℃ for 5-10 minutes; the high-frequency heating temperature of the aluminum alloy wire is higher than that of the titanium wire.
[0025] The titanium wire obtained after step three, which involves heating at different temperatures, has a rectangular cross-section with dimensions a1*b1; where a1 is the length and b1 is the width.
[0026] The cross-section of the aluminum alloy wire obtained after the three-stage differential heating treatment is a regular isosceles trapezoid with rectangular dimensions of a2*b2*h; in the regular isosceles trapezoid, a2 is the upper side length, b2 is the lower side length, and h is the height; b2 is 1.05-1.10 times a2.
[0027] The cross-section a1 of titanium wire is smaller than the cross-section b2 of aluminum alloy wire;
[0028] Step 4, Asynchronous Rolling Composite Processing: The aluminum alloy wire obtained from the isothermal heating treatment in Step 3 is fixed above the rolling mill, and the titanium wire obtained from the isothermal heating treatment in Step 3 is fixed below the rolling mill. The vertical bisecting plane along the length direction of the aluminum alloy wire coincides with the vertical bisecting plane along the length direction of the titanium wire. The upper surface area of the aluminum alloy wire is equal to the upper surface area of the titanium wire, and the lower surface area of the aluminum alloy wire is equal to the upper surface area of the titanium wire. The lower surface of the aluminum alloy wire and the upper surface of the titanium wire are rolled together, forming the connection interface between the aluminum alloy wire and the titanium wire. Asynchronous rolling is performed by controlling the feed speed. The feed speed of the aluminum alloy wire is controlled at V1 = 1.5-5 m / min, and the feed speed of the titanium wire is controlled at V2 = 3-10 m / min. The cross-section A1 of the aluminum alloy wire before asynchronous rolling, the cross-section A1' of the aluminum alloy wire after asynchronous rolling, the cross-section A2 of the titanium wire before asynchronous rolling, the cross-section A2' of the titanium wire after asynchronous rolling, the uniform discharge speed of the titanium-aluminum layered composite material is V, and the feeding of aluminum alloy wire and titanium wire satisfies the following formulas: A1×V1=A1'×V, A2×V2=A2'×V. The rolling mill is controlled to roll the titanium wire and aluminum alloy wire to form a rolling composite interface. During the rolling composite process of titanium wire and aluminum alloy wire, the titanium wire does not undergo plastic deformation, while the aluminum alloy wire undergoes plastic deformation during rolling. The rolling composite yields a semi-finished titanium-aluminum layered composite material. In the obtained semi-finished titanium-aluminum layered composite material, the aluminum alloy wire plastically deforms and coats the outer wall of the titanium wire.
[0029] Step 5, double-sided edge grinding: Sandpaper grinding removes the aluminum alloy wire covering the outer wall of the titanium wire, that is, sandpaper grinding removes the aluminum alloy layer attached to the upper side wall, lower side wall and bottom surface of the titanium wire.
[0030] Step 6, cutting and edge wrapping, straightening and shaping: The titanium-aluminum layered composite material obtained by double-sided edge grinding in step 5 is subjected to cutting and edge wrapping treatment. After the cutting edge is ground and chamfered, it is straightened and shaped to obtain the pre-finished titanium-aluminum layered composite material.
[0031] Step 7: Solution treatment, aging treatment, and multi-point constant speed straightening treatment to obtain the finished titanium-aluminum composite wire;
[0032] Step 8: The finished titanium-aluminum composite wire is bent, welded at both ends, and polished to form a titanium-aluminum alloy mobile phone frame.
[0033] The processing technology provided in this application is relatively simple and easy to operate, facilitating the industrial production of high-performance titanium-aluminum composite materials to meet the requirements of mobile phone frames for high interfacial bonding performance and high hardness. In the semi-finished titanium-aluminum layered composite material, the aluminum alloy wire plastically deforms and coats the outer wall of the titanium wire, preventing the release agent from entering the rolled composite interface between the two, thus preventing the rolled composite interface from being damaged by the release agent and ensuring the overall interfacial bonding strength and bonding stability.
[0034] Preferably, the roughness Ra of the surface-textured titanium wire obtained in step two is 1-4 micrometers; the roughness Ra of the surface-textured aluminum alloy wire obtained in step two is 2-5 micrometers; and the roughness of the surface-textured aluminum alloy wire obtained in step two is greater than the roughness of the surface-textured titanium wire obtained in step two.
[0035] Preferably, the roughness Ra of the surface-textured titanium wire obtained in step two is 3 micrometers; the roughness Ra of the surface-textured aluminum alloy wire obtained in step two is 5 micrometers.
[0036] By adopting the above technical solutions, it is beneficial to improve the interfacial bonding performance of titanium-aluminum composite materials.
[0037] Preferably, in step three, the wire is subjected to differential heating treatment: the titanium wire with surface roughening treatment in step two is subjected to high-frequency heating to 300-320℃ for 120s, and then held at 360-370℃ for 10min; at the same time, the aluminum alloy wire with surface roughening treatment in step two is subjected to high-frequency heating to 400-420℃ for 180s, and then held at 400-420℃ for 10min.
[0038] Preferably, step seven is specifically operated as follows: the pre-made titanium-aluminum layered composite material from step six is heated to 500-550℃ within 10-18 minutes and held for 20-40 minutes to complete the solution treatment. After cooling to room temperature for 15-30 minutes, an aging treatment is performed. The aging treatment is specifically operated as follows: the temperature is raised to 170-200℃ within 5-10 minutes and held for 3-5 hours. After cooling to room temperature for 15-30 minutes, a multi-point constant speed straightening treatment is performed to obtain the finished titanium-aluminum composite wire.
[0039] Preferably, step seven is specifically operated as follows: the pre-made titanium-aluminum layered composite material from step six is heated to 520°C within 15 minutes and held for 30 minutes to complete the solution treatment. After cooling to room temperature for 20 minutes, an aging treatment is performed. The aging treatment is specifically operated as follows: the temperature is raised to 185°C within 5 minutes and held for 4 hours. After cooling to room temperature for 30 minutes, a multi-point constant speed straightening treatment is performed to obtain the finished titanium-aluminum composite wire.
[0040] By adopting the above technical solutions, it is beneficial to improve the interfacial bonding performance of titanium-aluminum composite materials.
[0041] Preferably, in the asynchronous rolling composite process of step four, the titanium wire does not undergo plastic deformation during the rolling composite process of titanium wire and aluminum alloy wire, and the rolling deformation of aluminum alloy wire is 40-60%.
[0042] Preferably, in the asynchronous rolling composite process of step four, the titanium wire does not undergo plastic deformation and the rolling deformation of the aluminum alloy wire is 50% during the rolling composite process of titanium wire and aluminum alloy wire.
[0043] By adopting the above technical solutions, it is beneficial to improve the interfacial bonding performance of titanium-aluminum composite materials and the hardness of aluminum alloys.
[0044] In summary, this application has the following advantages:
[0045] 1. The interfacial bonding strength of the titanium-aluminum composite material prepared in this application is 180-220 MPa, the elongation is 18-20%, and the hardness of the aluminum alloy in the titanium-aluminum composite material is 118-128 HV, which meets the requirements of mobile phone frames for high interfacial bonding performance and high hardness of titanium-aluminum composite materials.
[0046] 2. The processing technology provided in this application breaks through the limitations of current strip profile rolling composite, realizes the preparation of titanium-aluminum composite materials by linear profile rolling composite technology, and the overall operation difficulty of the processing technology is low, which facilitates industrial production and manufacturing.
[0047] 3. This application conducts in-depth research on the titanium-aluminum interface. By introducing a nanoscale interface modifier, the interfacial compatibility and bonding strength of the rolled composite interface are effectively improved. This not only improves the interfacial peel strength, bending resistance and hardness of the prepared titanium-aluminum composite material, but also helps to eliminate internal stress and improve the overall fracture toughness. Attached Figure Description
[0048] Figure 1 This is a process flow diagram of a mobile phone frame based on titanium-aluminum composite material in an embodiment of this application.
[0049] Figure 2 This is a diagram illustrating the positioning structure of aluminum alloy wire and titanium wire before rolling composite processing in step four of this application embodiment.
[0050] Figure 3 This is a cross-sectional view of the semi-finished titanium-aluminum layered composite material after the asynchronous rolling composite treatment in step four and the double-sided edge grinding treatment in step five of this application. Detailed Implementation
[0051] To further understand the present invention, preferred embodiments are described below with reference to examples. However, it should be understood that these descriptions are merely for illustrating the features and advantages of the present invention and are not intended to limit the scope of the claims. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired results.
[0052] It is particularly important to note that all similar substitutions and modifications will be obvious to those skilled in the art and are considered to be included within the scope of this invention. The methods and applications of this invention have been described through preferred embodiments, and those skilled in the art will readily be able to modify or appropriately alter and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to implement and apply the technology of this invention. While it is believed that those skilled in the art will fully understand the following terms, the following definitions are set forth to help illustrate the subject matter disclosed in this invention.
[0053] As used herein, the term "comprising" is synonymous with "including," "containing," or "characterized in," and is inclusive of endpoints or open-ended, and does not exclude additional unstated elements or method steps. "Comprising" is a technical term used in the language of claims, meaning that the stated element is present, but other elements may be added and still form a construction or method within the scope of the claims.
[0054] Example
[0055] A mobile phone frame based on titanium-aluminum composite material is made of titanium-aluminum composite material. The titanium-aluminum composite material is made of titanium wire and aluminum alloy wire through wire surface cleaning treatment, wire surface roughening treatment, wire temperature heating treatment, asynchronous rolling composite, double-sided edge grinding, cutting and edge wrapping, straightening and shaping, solution treatment, aging treatment, and multi-point constant speed straightening treatment.
[0056] The titanium wire in the titanium-aluminum composite material is made of pure titanium wire or titanium alloy wire. The aluminum alloy wire in the titanium-aluminum composite material is Al-Si-Mg alloy wire or interface-modified Al-Si-Mg alloy wire. The interface-modified Al-Si-Mg alloy wire contains 0.2-2 wt% nano-scale interface modifier, with the balance being Al-Si-Mg alloy. The interfacial bonding strength of the titanium-aluminum composite material is 180-220 MPa, the elongation is 18-20%, and the hardness of the aluminum alloy in the titanium-aluminum composite material is 118-128 HV.
[0057] When the aluminum alloy wire in the titanium-aluminum composite material is an Al-Si-Mg alloy wire, then the Al-Si-Mg alloy wire is a 6-series aluminum alloy wire; when the aluminum alloy wire in the titanium-aluminum composite material is an interface-modified Al-Si-Mg alloy wire, then the Al-Si-Mg alloy wire in the interface-modified Al-Si-Mg alloy wire is a 6-series aluminum alloy wire.
[0058] Preferably, when the aluminum alloy wire in the titanium-aluminum composite material is an Al-Si-Mg alloy wire, the Al-Si-Mg alloy wire is one of 6061 aluminum alloy wire, 6063 aluminum alloy wire, and 6013 aluminum alloy wire; when the aluminum alloy wire in the titanium-aluminum composite material is an interface-modified Al-Si-Mg alloy wire, the Al-Si-Mg alloy wire in the interface-modified Al-Si-Mg alloy wire is one of 6061 aluminum alloy wire, 6063 aluminum alloy wire, and 6013 aluminum alloy wire.
[0059] Preferably, when the aluminum alloy wire in the titanium-aluminum composite material is an interface-modified Al-Si-Mg alloy wire, the Al-Si-Mg alloy wire in the interface-modified Al-Si-Mg alloy wire is an aluminum alloy wire made of 6013--T4-S-ST-1 aluminum alloy. The interface-modified Al-Si-Mg alloy wire contains 0.5-0.8 wt% of nano-scale interface modifier, with the balance being Al-Si-Mg alloy.
[0060] The average particle size of the nanoscale interface modifier is 50-200 nm.
[0061] The nanoscale interface modifier includes a carrier and over-plated metal elements that are fixed to the surface of the carrier in the form of single atoms via covalent bonds. The over-plated metal elements are Ti and Al, and the mass ratio of Ti to Al is (0.8-1.2):(0.8-1.2).
[0062] The carrier is at least one of MAX phase nano-ceramic powder, graphene, and carbon nanotubes. The MAX phase nano-ceramic powder is at least one of Ti2AlN nano-ceramic powder, Ti3AlC2 nano-ceramic powder, Ti3AlCN nano-ceramic powder, Ti2AlC nano-ceramic powder, and Al-Ti3AlC2 nano-ceramic powder. The doping rate of the overplated metal element in the nanoscale interface modifier is 5-10 wt%.
[0063] Preferably, the mass ratio of Ti to Al in the overplated metal elements is 1:1. The doping rate of the overplated metal elements in the nanoscale interface modifier is 8±0.5wt%; the carrier is composed of carbon nanotubes and / or graphene combined with Al-Ti3AlC2 nano-ceramic powder.
[0064] A processing technology for a mobile phone frame based on titanium-aluminum composite material includes the following steps:
[0065] Step 1, cleaning the wire surface:
[0066] The cross-section of titanium wire raw material is rectangular; the cross-section of aluminum alloy wire raw material is an isosceles trapezoid.
[0067] Titanium wires were subjected to ultrasonic cleaning with acetone, ultrasonic cleaning with deionized water, ultrasonic cleaning with acid, ultrasonic cleaning with deionized water, and low-temperature drying under nitrogen protection to obtain surface-cleaned titanium wires.
[0068] Meanwhile, aluminum alloy wires were subjected to ultrasonic cleaning with acetone, ultrasonic cleaning with deionized water, ultrasonic cleaning with acid, ultrasonic cleaning with deionized water, and low-temperature drying under nitrogen protection to obtain aluminum alloy wires with surface cleaning treatment.
[0069] Step 2, surface roughening treatment of the wire:
[0070] The titanium wire that underwent surface cleaning in step one was subjected to laser scanning texturing, followed by ultrasonic cleaning with acid solution, ultrasonic cleaning with deionized water, and low-temperature drying under nitrogen protection to obtain the surface-textured titanium wire.
[0071] Simultaneously, the aluminum alloy wire that underwent surface cleaning in step one is subjected to laser scanning texturing, followed by ultrasonic cleaning with acid solution, ultrasonic cleaning with deionized water, and low-temperature drying under nitrogen protection to obtain the surface-textured aluminum alloy wire.
[0072] Step 3, Differential Temperature Heating Treatment of Wires: The titanium wires that underwent surface roughening treatment in Step 2 are subjected to high-frequency heating to 300-400℃ for 100-120 seconds, followed by a holding treatment for 5-10 minutes at 360-390℃; simultaneously, the aluminum alloy wires that underwent surface roughening treatment in Step 2 are subjected to high-frequency heating to 400-460℃ for 160-200 seconds, followed by a holding treatment for 5-10 minutes at 400-440℃; the high-frequency heating temperature of the aluminum alloy wires is higher than that of the titanium wires;
[0073] The titanium wire obtained after the three-stage differential heating treatment has a rectangular cross-section with dimensions a1*b1; in the rectangle, a1 is the length and b1 is the width.
[0074] The cross-section of the aluminum alloy wire obtained after the three-stage differential heating treatment is a regular isosceles trapezoid with rectangular dimensions of a2*b2*h; in the regular isosceles trapezoid, a2 is the upper side length, b2 is the lower side length, and h is the height; b2 is 1.05-1.10 times a2.
[0075] The cross-section a1 of titanium wire is smaller than the cross-section b2 of aluminum alloy wire;
[0076] Step 4, Asynchronous Rolling Composite Processing: The aluminum alloy wire obtained from the isothermal heating treatment in Step 3 is fixed above the rolling mill, and the titanium wire obtained from the isothermal heating treatment in Step 3 is fixed below the rolling mill. The vertical bisecting plane along the length direction of the aluminum alloy wire coincides with the vertical bisecting plane along the length direction of the titanium wire. The upper surface area of the aluminum alloy wire is equal to the upper surface area of the titanium wire, and the lower surface area of the aluminum alloy wire is equal to the upper surface area of the titanium wire. The lower surface of the aluminum alloy wire and the upper surface of the titanium wire are rolled together, forming the connection interface between the aluminum alloy wire and the titanium wire. Asynchronous rolling is performed by controlling the feed speed. The feed speed of the aluminum alloy wire is controlled at V1 = 1.5-5 m / min, and the feed speed of the titanium wire is controlled at V2 = 3-10 m / min. The cross-section A1 of the aluminum alloy wire before asynchronous rolling, the cross-section A1' of the aluminum alloy wire after asynchronous rolling, the cross-section A2 of the titanium wire before asynchronous rolling, the cross-section A2' of the titanium wire after asynchronous rolling, the uniform discharge speed of the titanium-aluminum layered composite material is V, and the feeding of aluminum alloy wire and titanium wire satisfies the following formulas: A1×V1=A1'×V, A2×V2=A2'×V. The rolling mill is controlled to roll the titanium wire and aluminum alloy wire to form a rolling composite interface. During the rolling composite process of titanium wire and aluminum alloy wire, the titanium wire does not undergo plastic deformation, while the aluminum alloy wire undergoes plastic deformation during rolling. The rolling composite yields a semi-finished titanium-aluminum layered composite material. In the obtained semi-finished titanium-aluminum layered composite material, the aluminum alloy wire plastically deforms and coats the outer wall of the titanium wire.
[0077] Step 5, double-sided edge grinding: Sandpaper grinding removes the aluminum alloy wire covering the outer wall of the titanium wire, that is, sandpaper grinding removes the aluminum alloy layer attached to the upper side wall, lower side wall and bottom surface of the titanium wire.
[0078] Step 6, cutting and edge wrapping, straightening and shaping: The titanium-aluminum layered composite material obtained by double-sided edge grinding in step 5 is subjected to cutting and edge wrapping treatment. After the cutting edge is ground and chamfered, it is straightened and shaped to obtain the pre-finished titanium-aluminum layered composite material.
[0079] Step 7: Solution treatment, aging treatment, and multi-point constant speed straightening treatment to obtain the finished titanium-aluminum composite wire;
[0080] Step 8: The finished titanium-aluminum composite wire is bent, welded at both ends, and polished to form a titanium-aluminum alloy mobile phone frame.
[0081] Preferably, the roughness Ra of the surface-textured titanium wire obtained in step two is 1-4 micrometers; the roughness Ra of the surface-textured aluminum alloy wire obtained in step two is 2-5 micrometers; and the roughness of the surface-textured aluminum alloy wire obtained in step two is greater than that of the surface-textured titanium wire obtained in step two.
[0082] More preferably, the roughness Ra of the surface-textured titanium wire obtained in step two is 3 micrometers; the roughness Ra of the surface-textured aluminum alloy wire obtained in step two is 5 micrometers.
[0083] Preferably, in step three, the wire undergoes a differential temperature heating treatment: the titanium wire that underwent surface roughening treatment in step two is subjected to high-frequency heating to 300-320℃ for 120 seconds, followed by a heat treatment of 10 minutes at 360-370℃; simultaneously, the aluminum alloy wire that underwent surface roughening treatment in step two is subjected to high-frequency heating to 400-420℃ for 180 seconds, followed by a heat treatment of 10 minutes at 400-420℃.
[0084] Preferably, step seven is specifically operated as follows: the pre-made titanium-aluminum layered composite material from step six is heated to 500-550℃ within 10-18 minutes and held for 20-40 minutes to complete the solution treatment. After cooling to room temperature for 15-30 minutes, an aging treatment is performed. The specific operation of the aging treatment is as follows: the temperature is raised to 170-200℃ within 5-10 minutes and held for 3-5 hours. After cooling to room temperature for 15-30 minutes, a multi-point constant speed straightening treatment is performed to obtain the finished titanium-aluminum composite wire.
[0085] More preferably, step seven is specifically operated as follows: the pre-made titanium-aluminum layered composite material from step six is heated to 520℃ within 15 minutes and held for 30 minutes to complete the solution treatment. After cooling to room temperature for 20 minutes, the material is subjected to aging treatment. The specific operation of aging treatment is as follows: the material is heated to 185℃ within 5 minutes and held for 4 hours. After cooling to room temperature for 30 minutes, the material is subjected to multi-point constant speed straightening treatment to obtain the finished titanium-aluminum composite wire.
[0086] Preferably, in step four, asynchronous rolling composite processing, during the rolling composite process of titanium wire and aluminum alloy wire in the rolling mill, the titanium wire does not undergo plastic deformation, and the rolling deformation of the aluminum alloy wire is 40-60%.
[0087] More preferably, in step four, asynchronous rolling composite processing, during the rolling composite process of titanium wire and aluminum alloy wire in the rolling mill, the titanium wire does not undergo plastic deformation, and the rolling deformation of the aluminum alloy wire is 50%.
[0088] Example 1: A mobile phone frame based on titanium-aluminum composite material is made of titanium-aluminum composite material. The titanium-aluminum composite material is made from titanium wire and aluminum alloy wire through a process including wire surface cleaning, wire surface roughening, wire temperature heating, asynchronous rolling, double-sided edge grinding, edge cutting, straightening and shaping, solution treatment, aging treatment, and multi-point constant speed straightening. The titanium wire in the titanium-aluminum composite material is pure titanium wire. The aluminum alloy wire in the titanium-aluminum composite material is 6063-T6 aluminum alloy wire.
[0089] A processing technology for a mobile phone frame based on titanium-aluminum composite material includes the following steps:
[0090] Step 1, cleaning the wire surface:
[0091] The cross-section of titanium wire raw material is rectangular; the cross-section of 6063-T6 aluminum alloy wire raw material is an isosceles trapezoid.
[0092] Pure titanium wire was subjected to ultrasonic cleaning with acetone for 200s, ultrasonic cleaning with deionized water for 60s, ultrasonic cleaning with acid solution (5wt% hydrochloric acid) for 180s, ultrasonic cleaning with deionized water for 60s, and then dried at low temperature under nitrogen protection to obtain titanium wire with surface cleaning treatment; the ultrasonic cleaning power was 1200W and the ultrasonic cleaning frequency was 44kHz.
[0093] Meanwhile, the 6063-T6 aluminum alloy wire was subjected to ultrasonic cleaning with acetone for 200s, ultrasonic cleaning with deionized water for 60s, ultrasonic cleaning with acid solution (5wt% hydrochloric acid) for 180s, ultrasonic cleaning with deionized water for 60s, and low-temperature drying under nitrogen protection to obtain aluminum alloy wire with surface cleaning treatment; the ultrasonic cleaning power was 1200W and the ultrasonic cleaning frequency was 44kHz.
[0094] Step 2, surface roughening treatment of the wire:
[0095] The titanium wire that underwent surface cleaning in step one was subjected to laser scanning texturing, followed by ultrasonic cleaning with acid solution (5wt% hydrochloric acid) for 300s, ultrasonic cleaning with deionized water for 100s, and low-temperature drying under nitrogen protection to obtain the surface-textured titanium wire. The ultrasonic cleaning power was 1200W and the ultrasonic cleaning frequency was 44kHz. The roughness Ra of the obtained surface-textured titanium wire was 3 micrometers.
[0096] Simultaneously, the aluminum alloy wire that underwent surface cleaning in step one was subjected to laser scanning roughening treatment, followed by ultrasonic cleaning with acid solution (5wt% hydrochloric acid) for 240s, ultrasonic cleaning with deionized water for 100s, and low-temperature drying under nitrogen protection to obtain the surface roughened aluminum alloy wire; the roughness Ra of the obtained surface roughened aluminum alloy wire is 5 micrometers.
[0097] Step 3, wire temperature heating treatment: The titanium wire with surface roughening treatment in Step 2 is heated to 300℃ by high frequency for 120 seconds, and then held at 360℃ for 10 minutes; at the same time, the aluminum alloy wire with surface roughening treatment in Step 2 is heated to 400℃ by high frequency for 180 seconds, and then held at 400℃ for 10 minutes.
[0098] The titanium wire obtained after step three, which involves heating at different temperatures, has a rectangular cross-section with dimensions a1*b1. In the rectangle, a1 is the length and b1 is the width, and a1 = 0.8b1.
[0099] The aluminum alloy wire obtained after step three, which involves heating at different temperatures, has a cross-section that is an isosceles trapezoid with rectangular dimensions of a2*b2*h. In the isosceles trapezoid, a2 is the length of the upper side, b2 is the length of the lower side, and h is the height. b2 is 1.1 times the length of a2.
[0100] The cross-section a1 of titanium wire is smaller than the cross-section b2 of aluminum alloy wire;
[0101] Step 4, Asynchronous Rolling Composite Processing: The aluminum alloy wire obtained from the differential heating treatment in Step 3 is fixed above the rolling mill, and the titanium wire obtained from the differential heating treatment in Step 3 is fixed below the rolling mill. The vertical bisecting plane along the length of the aluminum alloy wire coincides with the vertical bisecting plane along the length of the titanium wire. The upper surface area of the aluminum alloy wire is equal to the upper surface area of the titanium wire, and the lower surface area of the aluminum alloy wire is equal to the upper surface area of the titanium wire. The lower surface of the aluminum alloy wire and the upper surface of the titanium wire are rolled together, forming the connection interface between the aluminum alloy wire and the titanium wire. Before asynchronous rolling, the cross-section A1 of the aluminum alloy wire is 10mm at the top, 11mm at the bottom, 10mm in height, and has an area of 105mm². 2 The cross-section A1' (48.3 mm) of the asynchronously rolled aluminum alloy wire is... 2 The cross-section A2 of the titanium wire before asynchronous rolling is 10mm*2mm=20mm. 2 The cross-section A2 of the asynchronously rolled titanium wire is 10mm*2mm=20mm. 2The uniform discharge speed of the titanium-aluminum layered composite material is V = 6.5 m / min. The feeding speed of the aluminum alloy wire and titanium wire satisfies the following formula: The outlet speed after composite is controlled at 6.5 m / min. The feeding speeds V1 (aluminum feed speed) and V2 (titanium feed speed) are determined by A1 × V1 = A1' × V (6.5 m / min) and A2 × V2 = A2' × V (6.5 m / min), respectively. Therefore, the aluminum feed speed V1 = 2.99 m / min, and the titanium feed speed... The feed rate V2 = 6.5 m / min is controlled to roll titanium wire and aluminum alloy wire together to form a rolling composite interface. During the rolling composite process of titanium wire and aluminum alloy wire, the titanium wire does not undergo plastic deformation, while the aluminum alloy wire undergoes plastic deformation. The rolling deformation of the aluminum alloy wire is 50%. The rolling composite yields a semi-finished titanium-aluminum layered composite material. In the obtained semi-finished titanium-aluminum layered composite material, the aluminum alloy wire plastic deformation covers the outer wall of the titanium wire.
[0102] Step 5, double-sided edge grinding: Sandpaper grinding removes the aluminum alloy wire covering the outer wall of the titanium wire, that is, sandpaper grinding removes the aluminum alloy layer attached to the upper side wall, lower side wall and bottom surface of the titanium wire.
[0103] Step 6, cutting and edge wrapping, straightening and shaping: The titanium-aluminum layered composite material obtained by double-sided edge grinding in step 5 is subjected to cutting and edge wrapping treatment. After the cutting edge is ground and chamfered, it is straightened and shaped to obtain the pre-finished titanium-aluminum layered composite material.
[0104] Step 7: Heat the pre-formed titanium-aluminum layered composite material from Step 6 to 520℃ within 15 minutes and hold for 30 minutes to complete the solution treatment. After cooling to room temperature for 20 minutes, perform aging treatment. The specific operation of aging treatment is as follows: heat to 185℃ within 5 minutes and hold for 4 hours. After cooling to room temperature for 30 minutes, perform multi-point constant speed straightening treatment to obtain the finished titanium-aluminum composite wire.
[0105] Step 8: Bend, weld the ends of the finished titanium-aluminum composite wire from Step 7, and polish it to make a titanium-aluminum alloy mobile phone frame.
[0106] The difference between Example 2 and Example 1 is that the roughness Ra of the surface-textured titanium wire obtained in step 2 is 1 micrometer, while the roughness Ra of the surface-textured aluminum alloy wire obtained in step 2 is 3 micrometers.
[0107] The difference between Example 3 and Example 1 is that the roughness Ra of the surface-textured titanium wire obtained in step 2 is 2 micrometers, while the roughness Ra of the surface-textured aluminum alloy wire obtained is 4 micrometers.
[0108] The difference between Example 4 and Example 1 is that the roughness Ra of the surface-textured titanium wire obtained in step two is 4 micrometers, while the roughness Ra of the surface-textured aluminum alloy wire obtained in step two is 5 micrometers.
[0109] The difference between Example 5 and Example 1 is as follows: Step 3, wire temperature heating treatment: The titanium wire with surface roughening treatment in Step 2 is subjected to high-frequency heating to 320°C for 120 seconds, and then held at 370°C for 10 minutes; At the same time, the aluminum alloy wire with surface roughening treatment in Step 2 is subjected to high-frequency heating to 420°C for 180 seconds, and then held at 420°C for 10 minutes.
[0110] The difference between Example 6 and Example 1 is as follows: Step 3, wire temperature heating treatment: The titanium wire with surface roughening treatment in Step 2 is subjected to high-frequency heating to 350°C for 120 seconds, and then held at 390°C for 10 minutes; At the same time, the aluminum alloy wire with surface roughening treatment in Step 2 is subjected to high-frequency heating to 440°C for 180 seconds, and then held at 440°C for 10 minutes.
[0111] The difference between Example 7 and Example 1 is as follows: Step 3, wire temperature heating treatment: The titanium wire with surface roughening treatment in Step 2 is subjected to high-frequency heating to 390°C for 120 seconds, and then held at 390°C for 10 minutes; At the same time, the aluminum alloy wire with surface roughening treatment in Step 2 is subjected to high-frequency heating to 460°C for 180 seconds, and then held at 460°C for 10 minutes.
[0112] The difference between Example 8 and Example 1 is as follows: In step four, the uniform discharge speed of the titanium-aluminum layered composite material is V = 5 m / min. The feeding of aluminum alloy wire and titanium wire satisfies the following formula: the outlet speed after composite is controlled to be 5 m / min. The feeding speed V1 - aluminum feeding speed and V2 - titanium feeding speed are determined by A1×V1 = A1'×V (5 m / min) and A2×V2 = A2'×V (5 m / min). The aluminum feeding speed V1 = 2.3 m / min and the titanium feeding speed V2 = 5 m / min can be calculated.
[0113] The difference between Example 9 and Example 1 is as follows: In step four, the uniform discharge speed of the titanium-aluminum layered composite material is V = 4 m / min. The feeding of aluminum alloy wire and titanium wire satisfies the following formula: the outlet speed after composite is controlled to be 4 m / min. The feeding speed V1 - aluminum feeding speed and V2 - titanium feeding speed are determined by A1×V1 = A1'×V (4 m / min) and A2×V2 = A2'×V (4 m / min). The aluminum feeding speed V1 = 1.84 m / min and the titanium feeding speed V2 = 4 m / min can be calculated.
[0114] The difference between Example 10 and Example 1 is as follows: In step four, the uniform discharge speed of the titanium-aluminum layered composite material is V = 3 m / min. The feeding of aluminum alloy wire and titanium wire satisfies the following formula: the outlet speed after composite is controlled to be 3 m / min. The feeding speed V1 - aluminum feeding speed and V2 - titanium feeding speed are determined by A1×V1 = A1'×V (3 m / min) and A2×V2 = A2'×V (3 m / min). The aluminum feeding speed V1 = 1.38 m / min and the titanium feeding speed V2 = 3 m / min can be calculated.
[0115] The difference between Example 11 and Example 1 is that during the rolling composite process of titanium wire and aluminum alloy wire in the rolling mill, the titanium wire does not undergo plastic deformation, while the aluminum alloy wire undergoes plastic deformation during rolling. The rolling deformation of the aluminum alloy wire is 40%, and the semi-finished titanium-aluminum layered composite material is obtained by rolling composite.
[0116] The difference between Example 12 and Example 1 is that during the rolling composite process of titanium wire and aluminum alloy wire in the rolling mill, the titanium wire does not undergo plastic deformation, while the aluminum alloy wire undergoes plastic deformation during rolling. The rolling deformation of the aluminum alloy wire is 60%, and the semi-finished titanium-aluminum layered composite material is obtained by rolling composite.
[0117] The difference between Example 13 and Example 1 is as follows: In step seven, the pre-formed titanium-aluminum layered composite material from step six is heated to 500°C within 15 minutes and held for 30 minutes to complete the solution treatment. After cooling to room temperature for 20 minutes, an aging treatment is performed. The specific operation of the aging treatment is as follows: the temperature is raised to 170°C within 5 minutes and held for 4 hours. After cooling to room temperature for 30 minutes, a multi-point constant speed straightening treatment is performed to obtain the finished titanium-aluminum composite wire.
[0118] The difference between Example 14 and Example 1 is as follows: In step seven, the pre-made titanium-aluminum layered composite material from step six is heated to 540°C within 15 minutes and held for 30 minutes to complete the solution treatment. After cooling to room temperature for 20 minutes, an aging treatment is performed. The specific operation of the aging treatment is as follows: the temperature is raised to 180°C within 5 minutes and held for 4 hours. After cooling to room temperature for 30 minutes, a multi-point constant speed straightening treatment is performed to obtain the finished titanium-aluminum composite wire.
[0119] The difference between Example 15 and Example 1 is as follows: In step seven, the pre-formed titanium-aluminum layered composite material from step six is heated to 550°C within 15 minutes and held for 30 minutes to complete the solution treatment. After cooling to room temperature for 20 minutes, an aging treatment is performed. The specific operation of the aging treatment is as follows: the temperature is raised to 170°C within 5 minutes and held for 4 hours. After cooling to room temperature for 30 minutes, a multi-point constant speed straightening treatment is performed to obtain the finished titanium-aluminum composite wire.
[0120] The difference between Example 16 and Example 1 is as follows: In step seven, the pre-made titanium-aluminum layered composite material from step six is heated to 550°C within 15 minutes and held for 30 minutes to complete the solution treatment. After cooling to room temperature for 20 minutes, an aging treatment is performed. The specific operation of the aging treatment is as follows: the temperature is raised to 200°C within 5 minutes and held for 4 hours. After cooling to room temperature for 30 minutes, a multi-point constant speed straightening treatment is performed to obtain the finished titanium-aluminum composite wire.
[0121] The difference between Example 17 and Example 1 is that the aluminum alloy wire in the titanium-aluminum composite material is 6061-T6 aluminum alloy wire.
[0122] The difference between Example 18 and Example 1 is that the aluminum alloy wire in the titanium-aluminum composite material is made of 6013--T4-S-ST-1 aluminum alloy.
[0123] The difference between Example 19 and Example 1 is that the aluminum alloy wire in the titanium-aluminum composite material is an interface-modified Al-Si-Mg alloy wire. The interface-modified Al-Si-Mg alloy wire contains 0.1 wt% nano-scale interface modifier, with the balance being 6013-T4-S-ST-1 aluminum alloy. The interface-modified Al-Si-Mg alloy wire is formed by conventional melt casting of 99.9 wt% 6013-T4-S-ST-1 aluminum alloy and 0.1 wt% nano-scale interface modifier to form an aluminum alloy rod. The alloy rod is then subjected to T6 treatment (heating at 30℃ / min to 440℃, holding for 30 min, naturally cooling to room temperature for 30 min, then heating at 20℃ / min to 170℃, holding for 5 h, and naturally cooling to room temperature). The resulting product is the interface-modified Al-Si-Mg alloy wire used in the extrusion processing cost application for the nano-scale interface modifier-modified 6013-T4-S-ST-1 aluminum alloy rod. The average particle size of the nanoscale interface modifier is 200 nm. The nanoscale interface modifier comprises a carrier and over-plated metal elements fixed to the carrier surface via covalent bonds in single-atom form. The over-plated metal elements are Ti and Al, with a Ti / Al mass ratio of 1:1. The carrier is graphene, specifically three-dimensional graphene (TN3DPRGO) from Chengdu Institute of Organic Chemistry, Chinese Academy of Sciences, with a purity >96, 3-4 layers, a thickness of 1.3-1.4 nm, and a size of 6-8 μm.
[0124] The preparation method of nanoscale interface modifiers (disclosed as prior art to facilitate the reader's understanding of the technical solution) is as follows:
[0125] Step 1: 0.2g of graphene and 100g of acetone aqueous solution (5g acetone + 95g distilled water) are stirred at high speed to form a graphene dispersion. Simultaneously, 0.2g of potassium hydroxide (KOH) and 4.8g of distilled water are mixed evenly until the potassium hydroxide (KOH) is fully dissolved to obtain a 5.0wt% potassium hydroxide (KOH) aqueous solution. The graphene dispersion prepared above and 16g of the 6.0wt% potassium hydroxide (KOH) aqueous solution are added to a 250mL glass beaker, stirred evenly, and allowed to stand for 5 minutes. The glass beaker is then placed in an ultrasonic cleaner for 80 minutes of ultrasonic dispersion treatment at an ultrasonic power of 800W and an ultrasonic frequency of 60kHz. After ultrasonic dispersion treatment, the powder is vacuum filtered. The powder obtained by vacuum filtration is dried at 80℃ for 6 hours. The dried powder is then placed in a planetary ball mill for low-speed wet ball milling treatment at a liquid-to-material ratio of 1:5, a ball milling speed of 60rpm, and a ball milling time of 100 minutes to obtain activated graphene mixed powder.
[0126] Step 2: 1g of the activated graphene mixed powder prepared in Step 1 is loaded into crucible A; simultaneously, 0.98g of aluminum nitrate nonahydrate and 0.28g of titanium tetrachloride are mixed to form a metal salt (the mass ratio of Al in aluminum nitrate nonahydrate to Ti in titanium tetrachloride is 1:1) and loaded into crucible B. Crucible B has two integral support areas with an area ratio of 1:1. Aluminum nitrate nonahydrate and titanium tetrachloride are filled into the support areas of crucible B to complete the loading of the metal salt into crucible B; crucible A and crucible B are loaded into a sealed tube furnace, with crucible A located downstream of crucible B. Under Ar atmosphere protection, crucible A is heated to 640℃ at 10℃ / min and held for 180min to obtain the metal single-atom doped graphene precursor;
[0127] Step 3: The metal single-atom doped graphene precursor from Step 2 is placed in a 0.1 mol / L dilute hydrochloric acid aqueous solution and then ultrasonically cleaned for 60 minutes in an ultrasonic cleaner (ultrasonic power 800W, ultrasonic frequency 44kHz). It is then vacuum filtered and washed with distilled water until neutral. The resulting solid powder is dried at 80℃ for 12 hours. The dried powder is then subjected to low-speed wet ball milling in a planetary ball mill for refinement. The liquid-to-material ratio is 1:5, the ball milling speed is 60 rpm, and the milling time is 150 minutes to obtain the average particle size D. 50 A 200nm nanoscale interface modifier was obtained. The total content of overplated metal elements Al and Ti in the obtained nanoscale interface modifier was 6.42wt%.
[0128] The nanoscale interface modifier was prepared by Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences.
[0129] The difference between Example 20 and Example 19 is that the aluminum alloy wire in the titanium-aluminum composite material is an interface-modified Al-Si-Mg alloy wire. The interface-modified Al-Si-Mg alloy wire contains 0.2 wt% nano-scale interface modifier, with the balance being 6013--T4-S-ST-1-aluminum alloy.
[0130] The difference between Example 21 and Example 19 is that the aluminum alloy wire in the titanium-aluminum composite material is an interface-modified Al-Si-Mg alloy wire. The interface-modified Al-Si-Mg alloy wire contains 0.7 wt% nano-scale interface modifier, with the balance being 6013--T4-S-ST-1-aluminum alloy.
[0131] The difference between Example 22 and Example 19 is that the aluminum alloy wire in the titanium-aluminum composite material is an interface-modified Al-Si-Mg alloy wire. The interface-modified Al-Si-Mg alloy wire contains 1.5 wt% nano-scale interface modifier, with the balance being 6013--T4-S-ST-1-aluminum alloy.
[0132] The difference between Example 23 and Example 19 is that the aluminum alloy wire in the titanium-aluminum composite material is an interface-modified Al-Si-Mg alloy wire. The interface-modified Al-Si-Mg alloy wire contains 2.0 wt% nano-scale interface modifier, with the balance being 6013--T4-S-ST-1-aluminum alloy.
[0133] The difference between Example 24 and Example 21 lies in the preparation method of the nanoscale interface modifier. In step two, 1g of the activated graphene mixed powder prepared in step one is loaded into crucible A; simultaneously, 1.18g of aluminum nitrate nonahydrate and 0.41g of titanium tetrachloride are mixed to form a metal salt (the mass ratio of Al in aluminum nitrate nonahydrate to Ti in titanium tetrachloride is 1:1) and loaded into crucible B. Crucible B has two integrally formed support areas with an area ratio of 1:1. Aluminum nitrate nonahydrate and titanium tetrachloride are filled into the support areas of crucible B, thus completing the loading of the metal salt into crucible B. Crucibles A and B are placed in a sealed tube furnace, with crucible A located downstream of crucible B. Under Ar atmosphere protection, crucible A is heated to 640℃ at 10℃ / min and held for 180min to obtain the metal single-atom doped graphene precursor. The total content of over-plated metal elements Al and Ti in the obtained nanoscale interface modifier is 8.25wt%.
[0134] The difference between Example 25 and Example 21 lies in the preparation method of the nanoscale interface modifier. In step two, 1g of the activated graphene mixed powder prepared in step one is loaded into crucible A; simultaneously, 2.128g of aluminum nitrate nonahydrate and 0.58g of titanium tetrachloride are mixed to form a metal salt (the mass ratio of Al in aluminum nitrate nonahydrate to Ti in titanium tetrachloride is 1:1) and loaded into crucible B. Crucible B has two integrally formed support areas with an area ratio of 1:1. Aluminum nitrate nonahydrate and titanium tetrachloride are filled into the support areas of crucible B, thus completing the loading of the metal salt into crucible B. Crucibles A and B are placed in a sealed tube furnace, with crucible A located downstream of crucible B. Under Ar atmosphere protection, crucible A is heated to 640℃ at 10℃ / min and held for 180min to obtain the metal single-atom doped graphene precursor. The total content of over-plated metal elements Al and Ti in the obtained nanoscale interface modifier is 9.87wt%.
[0135] The difference between Example 26 and Example 21 lies in the preparation method of the nanoscale interface modifier. In step two, 1g of the activated graphene mixed powder prepared in step one is loaded into crucible A; simultaneously, 0.51g of aluminum nitrate nonahydrate and 0.15g of titanium tetrachloride are mixed to form a metal salt (the mass ratio of Al in aluminum nitrate nonahydrate to Ti in titanium tetrachloride is 1:1) and loaded into crucible B. Crucible B has two integrally formed support areas with an area ratio of 1:1. Aluminum nitrate nonahydrate and titanium tetrachloride are filled into the support areas of crucible B, thus completing the loading of the metal salt into crucible B. Crucibles A and B are placed in a sealed tube furnace, with crucible A located downstream of crucible B. Under Ar atmosphere protection, crucible A is heated to 640℃ at 10℃ / min and held for 180min to obtain the metal single-atom doped graphene precursor. The total content of over-plated metal elements Al and Ti in the obtained nanoscale interface modifier is 3.81wt%.
[0136] The difference between Example 27 and Example 21 lies in the preparation method of the nanoscale interface modifier. In step two, 1g of the activated graphene mixed powder prepared in step one is loaded into crucible A; simultaneously, a metal salt formed by mixing 2.93g of aluminum nitrate nonahydrate and 0.84g of titanium tetrachloride (the mass ratio of Al in aluminum nitrate nonahydrate to Ti in titanium tetrachloride is 1:1) is loaded into crucible B. Crucible B has two integrally formed support areas with an area ratio of 1:1. Aluminum nitrate nonahydrate and titanium tetrachloride are filled into the support areas of crucible B, thus completing the loading of the metal salt into crucible B. Crucibles A and B are placed in a sealed tube furnace, with crucible A located downstream of crucible B. Under Ar atmosphere protection, crucible A is heated to 640℃ at 10℃ / min and held for 180min to obtain the metal single-atom doped graphene precursor. The total content of over-plated metal elements Al and Ti in the obtained nanoscale interface modifier is 11.21wt%.
[0137] The difference between Example 28 and Example 21 is that the interface-modified Al-Si-Mg alloy wire is formed by conventional melt casting of 98.5 wt% 6013-T4-S-ST-1-aluminum alloy, 1 wt% graphene-based nanoscale interface modifier prepared in Example 21, and 0.5 wt% MAX phase nano-ceramic powder-based nanoscale interface modifier to form an aluminum alloy rod. The alloy rod is then subjected to T6 treatment (heating at 30℃ / min to 440℃ and holding for 30 min, then naturally cooling to room temperature for 30 min, then heating at 20℃ / min to 170℃ and holding for 5 h, then naturally cooling to room temperature). The resulting product is the interface-modified Al-Si-Mg alloy wire used in the extrusion processing cost application for the 6013-T4-S-ST-1-aluminum alloy rod modified by nanoscale interface modifier.
[0138] The preparation method of MAX phase nano-ceramic powder-based nanoscale interface modifier is as follows: Surface activation treatment of Al-Ti3AlC2 nano-ceramic powder (customized by Beijing Beike New Material Technology Co., Ltd.) with malic acid is used to locate the defect sites. 10g of Al-Ti3AlC2 nano-ceramic powder is immersed in a 20wt% tartaric acid aqueous solution (20g malic acid + 80g deionized oil) for 6 hours. After drying, it is immersed in a metal impregnation solution (5g aluminum nitrate nonahydrate and 1.4g titanium tetrachloride solvent are dissolved in 93.6g distilled water to form...). The sample was soaked in a metal immersion solution for 3 hours, followed by ultrasonic dispersion for 3 hours. The ultrasonic power was 1200W and the ultrasonic frequency was 44kHz. The sample was then removed, filtered, and dried to obtain a solid. The solid was then wet-milled at low speed using a planetary ball mill to obtain a powder with an average particle size of 200nm. The obtained powder was placed in a muffle furnace and heated at a rate of 3℃ / min until it reached 580℃ and was held for calcination for 12 hours. The obtained solid was then wet-milled at low speed using a planetary ball mill to obtain a MAX phase nano-ceramic powder-based nanoscale interface modifier with an average particle size of 200nm.
[0139] The difference between Example 29 and Example 28 is the different formulation of the interface-modified Al-Si-Mg alloy wire. The interface-modified Al-Si-Mg alloy wire in this example is made of 99.3 wt% 6013-T4-S-ST-1-aluminum alloy, 0.45 wt% graphene-based nanoscale interface modifier prepared in Example 21, and 0.25 wt% MAX phase nano-ceramic powder-based nanoscale interface modification from Example 28.
[0140] Comparative Example
[0141] The difference between Comparative Example 1 and Example 1 is that the wire surface roughening treatment in step two was not performed, while the wire surface cleaning treatment in step one was directly subjected to wire temperature heating treatment.
[0142] The difference between Comparative Example 2 and Example 1 is that the roughness of the titanium wire with surface texturing treatment obtained in step two is Ra3, and the roughness of the aluminum alloy wire with surface texturing treatment obtained is Ra3.
[0143] The difference between Comparative Example 3 and Example 1 is that the surface cleaning treatment of the wire in step 1 was not performed before the surface roughening treatment of the wire in step 2.
[0144] The difference between Comparative Example 4 and Example 1 is as follows: In step three, the wire is heated at the same temperature: the titanium wire with surface roughening treatment in step two is heated to 400°C by high frequency for 120 seconds, and then held at 400°C for 10 minutes; at the same time, the aluminum alloy wire with surface roughening treatment in step two is heated to 400°C by high frequency for 180 seconds, and then held at 400°C for 10 minutes.
[0145] The difference between Comparative Example 5 and Example 1 is that in step four, during the asynchronous rolling composite process, the feeding speed of the aluminum alloy wire is controlled at V1 = 6 m / min, and the feeding speed of the titanium wire is controlled at V2 = 9 m / min.
[0146] The difference between Comparative Example 6 and Example 1 is that during the rolling composite process of titanium wire and aluminum alloy wire in the rolling mill, the titanium wire does not undergo plastic deformation, while the aluminum alloy wire undergoes plastic deformation during rolling. The rolling deformation of the aluminum alloy wire is 30%, and the semi-finished titanium-aluminum layered composite material is obtained by rolling composite.
[0147] Performance testing
[0148] 1. Interface bonding strength test: The titanium-aluminum layered composite materials prepared in Examples 1-4 and Comparative Examples 1-4 were used as samples. The samples were cut into strips of 15mm×2mm×2mm. The bonding strength of the samples was measured using a WDW-5 tensile testing machine. Each sample was tested 5 times, and the average value of the test results was taken.
[0149] 2. Bending test: Use a bending machine to bend the sample, and observe whether delamination occurs on the cross-section after it breaks.
[0150] 3. Aluminum alloy hardness test method: The hardness of aluminum alloy was determined using a Shanghai Yizong HV-1000 microhardness tester.
[0151] 4. Elongation test method: The elongation rate is determined by tensile testing using an XWW-20A universal tensile testing machine.
[0152] Data Analysis
[0153] Table 1 shows the test parameters of the titanium-aluminum composite materials in Examples 1-4 and Comparative Examples 1-3.
[0154] Aluminum alloy hardness HV Interfacial bonding strength (MPa) elongation % Is it layered? Example 1 121 189 18.6 no Example 2 118 182 18.2 no Example 3 118 184 18.5 no Example 4 120 188 18.4 no Comparative Example 1 115 172 17.5 yes Comparative Example 2 116 176 18.1 no Comparative Example 3 112 171 17.2 yes
[0155] Based on Examples 1-4 and Comparative Examples 1-3, and in conjunction with Table 1, it can be seen that, compared with Comparative Example 1, the use of step two, wire surface roughening treatment, in the processing technology can improve the interfacial compatibility of titanium-aluminum composite materials, enhance the interfacial bonding strength, and also have a positive effect on improving the hardness and ductility of aluminum alloy in titanium-aluminum composite materials.
[0156] Based on Examples 1-4 and Comparative Examples 1-3, and in conjunction with Table 1, it can be seen that, compared with Comparative Example 2, the roughness of the titanium wire after surface roughening treatment in Step 2 is Ra1-4; the roughness of the aluminum alloy wire obtained in Step 2 is Ra3-5. Furthermore, the roughness of the aluminum alloy wire is greater than that of the titanium wire. The prepared titanium-aluminum composite material exhibits good interfacial compatibility and high interfacial bonding strength, meeting the requirement of ≥180MPa. Additionally, the aluminum alloy in the titanium-aluminum composite material also exhibits relatively good hardness and ductility, satisfying the requirements of high interfacial bonding performance and high hardness for mobile phone frames.
[0157] Combining Examples 1-4 and Comparative Examples 1-3 with Table 1, it can be seen that, compared with Comparative Example 3, the surface cleaning treatment of the wire in the processing step can improve the interfacial compatibility of the titanium-aluminum composite material, enhance the interfacial bonding strength, and also positively improve the hardness and ductility of the aluminum alloy in the titanium-aluminum composite material. This indicates that impurities such as oxides, dust, and organic matter on the wire surface have a significant detrimental effect on the interfacial strength of the titanium-aluminum composite material, and also have a significant detrimental effect on the overall hardness, ductility, and mechanical strength of the titanium-aluminum composite material. Therefore, the surface cleaning treatment of the wire in step one is essential.
[0158] Table 2 shows the test parameters of the titanium-aluminum composite materials in Examples 1, 5-7, and Comparative Example 4.
[0159] Aluminum alloy hardness HV Interfacial bonding strength (MPa) elongation % Is it layered? Example 1 121 189 18.6 no Example 5 122 192 18.1 no Example 6 120 190 18.4 no Example 7 118 188 18.9 no Comparative Example 4 115 175 16.9 no
[0160] Based on Examples 1, 5-7, and Comparative Examples 1-4, and in conjunction with Table 2, it can be seen that the titanium-aluminum composite material prepared by the heterothermal heating treatment method in the processing technology has relatively better interfacial compatibility and interfacial bonding strength, and better overall performance.
[0161] Based on Examples 1, 5-7, and Comparative Examples 1-4, and in conjunction with Table 2, it can be seen that, compared with Examples 5-7, the difference between the high-frequency heating temperature of titanium wire and the high-frequency heating temperature of aluminum alloy wire, as well as the difference between the heat preservation temperature of titanium wire and the heat preservation temperature of aluminum alloy wire, have a significant impact on the interfacial bonding strength, hardness, and elongation uniformity of titanium-aluminum composite materials. Preferably, in step three, the wire undergoes heterogeneous heating treatment: the titanium wire that underwent surface roughening treatment in step two is subjected to high-frequency heating to 300-400℃ for 100-120s, followed by heat treatment for 5-10min at 360-390℃; simultaneously, the aluminum alloy wire that underwent surface roughening treatment in step two is subjected to high-frequency heating to 400-460℃ for 160-200s, followed by heat treatment for 5-10min at 400-440℃. The high-frequency heating temperature of the aluminum alloy wire is higher than that of the titanium wire, and the titanium-aluminum composite material prepared with a high-frequency heating temperature difference of 70-100℃ exhibits superior comprehensive performance.
[0162] Table 3 shows the test parameters of the titanium-aluminum composite materials in Examples 1, 8-12, and Comparative Examples 5-6.
[0163] Aluminum alloy hardness HV Interfacial bonding strength (MPa) elongation % Is it layered? Example 1 121 189 18.6 no Example 8 121 187 18.8 no Example 9 119 188 18.5 no Example 10 118 182 18.2 no Example 11 120 186 19.1 no Example 12 119 185 18.2 no Comparative Example 5 115 178 18.0 no Comparative Example 6 112 169 17.7 yes
[0164] Combining Examples 1, 8-12, and Comparative Examples 5-6 with Table 3, it can be seen that, compared with Comparative Example 5, Examples 1 and 8-10 show that when the feeding of aluminum alloy wire and titanium wire satisfies the following formulas: A1×V1=A1'×V, A2×V2=A2'×V, controlling the feeding speed V1 of the aluminum alloy wire and the feeding speed V2 of the titanium wire can improve the comprehensive performance of the prepared titanium-aluminum composite material. The interfacial bonding strength of the titanium-aluminum composite material in Examples 1 and 8-10 is ≥180MPa, the hardness of the aluminum alloy is ≥118HV, and the elongation is ≥18.0%, meeting the requirements of mobile phone frames for high interfacial bonding performance and high hardness of titanium-aluminum composite materials. The preferred solution is the titanium-aluminum composite material prepared by the processing technology of Example 1 or 8.
[0165] Based on Examples 1, 8-12, and Comparative Examples 5-6, and referring to Table 3, it can be seen that, compared with Comparative Example 6, in step four, the asynchronous rolling composite processing ensures that the titanium wire does not undergo plastic deformation during the rolling composite process of titanium wire and aluminum alloy wire (the dimensions of the titanium wire in the customer-customized product remain unchanged, i.e., it is necessary to ensure that the titanium wire does not undergo plastic deformation; the overall dimensions of the finished product are adjusted by changing the thickness of the aluminum alloy layer). The rolling deformation of the aluminum alloy wire is 40-60%, resulting in a titanium-aluminum composite material with superior comprehensive performance. When the rolling deformation of the aluminum alloy wire is less than 40%, it leads to a significant decrease in the interfacial bonding strength and the hardness of the aluminum alloy in the prepared titanium-aluminum composite material. Preferably, under the processing technology provided in this application, the rolling deformation of the aluminum alloy wire is preferably 50%.
[0166] Table 4 shows the test parameters of the titanium-aluminum composite materials in Examples 1 and 13-16, and Control Group 1.
[0167] Aluminum alloy hardness HV Interfacial bonding strength (MPa) elongation % Is it layered? Example 1 121 189 18.6 no Example 13 120 185 18.9 no Example 14 122 188 18.5 no Example 15 122 186 18.3 no Example 16 123 188 18.1 no Control group 1 116 176 18.2 no
[0168] The difference between Control Group 1 and Example 1 is as follows: In step seven, the pre-made titanium-aluminum layered composite material from step six is heated to 470°C within 15 minutes and kept at that temperature for 30 minutes to complete the solution treatment. After cooling to room temperature for 20 minutes, the material is then subjected to aging treatment. The specific operation of the aging treatment is as follows: the material is heated to 170°C within 5 minutes and kept at that temperature for 4 hours. After cooling to room temperature for 30 minutes, the material is then subjected to multi-point constant speed straightening treatment to obtain the finished titanium-aluminum composite wire.
[0169] Based on Examples 1, 13-16, and Control Group 1, and in conjunction with Table 3, it can be seen that the titanium-aluminum composite material prepared using the solution treatment + aging treatment provided in this application exhibits superior overall performance. The preferred solution treatment + aging treatment process is as follows: The pre-formed titanium-aluminum layered composite material from step six is heated to 520℃ within 15 minutes and held for 30 minutes to complete the solution treatment. After cooling to room temperature for 20 minutes, aging treatment is performed. The specific aging treatment operation involves heating to 185℃ within 5 minutes and holding for 4 hours. After cooling to room temperature for 30 minutes, multi-point constant-speed straightening treatment is performed to obtain the finished titanium-aluminum composite wire.
[0170] Table 5 shows the test parameters of the titanium-aluminum composite materials in Examples 1 and 17-28.
[0171]
[0172]
[0173] Based on Example 1 and Comparative Examples 17-28, and in conjunction with Table 5, it can be seen that, compared with Examples 17-18, the titanium-aluminum composite material prepared using 6013 aluminum alloy wire has relatively better overall performance.
[0174] Based on Example 1 and Comparative Examples 17-28, and referring to Table 5, it can be seen that, compared with Examples 19-23, the optimal addition amount of nano-scale interface modifier in the interface-modified Al-Si-Mg alloy wire is 0.2-2 wt%. Addition amounts below 0.2% do not significantly improve the overall performance of the prepared titanium-aluminum composite material. Excessive addition significantly improves the overall performance, but when the addition amount exceeds 1.5 wt%, the improvement trend slows down. This is because the cost of nano-scale interface modifiers is relatively high, resulting in a poor cost advantage for excessive addition. Considering the economic efficiency of the process, the presence of 0.5-0.8 wt% nano-scale interface modifier in the interface-modified Al-Si-Mg alloy wire ensures relatively superior overall performance of the prepared titanium-aluminum composite material.
[0175] Based on Example 1 and Comparative Examples 17-28, and referring to Table 5, it can be seen that, compared with Examples 24-27, Example 21 shows that the overall performance of the prepared titanium-aluminum composite material is relatively superior when the doping rate of the over-plated metal element in the nanoscale interface modifier is 5-10 wt%. Preferably, the doping rate of the over-plated metal element in the nanoscale interface modifier is 8.0 ± 0.5 wt%.
[0176] Based on Example 1 and Comparative Examples 17-28, and in conjunction with Table 5, it can be seen that, compared with Example 29 and Example 28, the titanium-aluminum composite material prepared by the composite nanoscale interface modifier consisting of MAX phase nano-ceramic powder-based nanoscale interface modifier and graphene-based nanoscale interface modifier has relatively superior comprehensive performance.
[0177] In summary, the processing technology provided in this application overcomes the limitations of current strip profile rolling composite technology, realizing the preparation of titanium-aluminum composite materials using linear profile rolling composite technology. The overall operation of the processing technology is relatively simple, facilitating industrial-scale manufacturing. Furthermore, the prepared titanium-aluminum composite material exhibits an interfacial bonding strength of 180-220 MPa, an elongation of 18-20%, and an aluminum alloy hardness of 118-128 HV, meeting the requirements of mobile phone frames for high interfacial bonding performance and high hardness of titanium-aluminum composite materials.
[0178] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A mobile phone frame based on titanium-aluminum composite material, characterized by: The mobile phone frame is made of a titanium-aluminum composite material; the titanium-aluminum composite material is made of titanium wire and aluminum alloy wire through wire surface cleaning treatment, wire surface roughening treatment, wire different temperature heating treatment, asynchronous rolling composite, double-sided edging, cutting and hemming, straightening and shaping, solid solution treatment, aging treatment, and multi-point constant speed straightening treatment; the titanium wire in the titanium-aluminum composite material is pure titanium wire or titanium alloy wire; the aluminum alloy wire in the titanium-aluminum composite material is Al-Si-Mg alloy wire or interface modified Al-Si-Mg alloy wire; the interface modified Al-Si-Mg alloy wire contains 0.2-2wt% of nano-level interface modifier, and the balance is Al-Si-Mg alloy; the interface bonding strength of the titanium-aluminum composite material is 180-220MPa, the elongation is 18-20%, and the hardness of the aluminum alloy in the titanium-aluminum composite material is 118-128HV.
2. The mobile phone frame based on titanium-aluminum composite material according to claim 1, characterized in that: When the aluminum alloy wire in the titanium-aluminum composite material is an Al-Si-Mg alloy wire, the Al-Si-Mg alloy wire is a 6 series aluminum alloy wire; when the aluminum alloy wire in the titanium-aluminum composite material is an interface-modified Al-Si-Mg alloy wire, the Al-Si-Mg alloy wire in the interface-modified Al-Si-Mg alloy wire is a 6 series aluminum alloy wire.
3. The mobile phone frame based on titanium-aluminum composite material according to claim 2, characterized in that: When the aluminum alloy wire in the titanium-aluminum composite material is an Al-Si-Mg alloy wire, the Al-Si-Mg alloy wire is one of 6061 aluminum alloy wire, 6063 aluminum alloy wire, and 6013 aluminum alloy wire; when the aluminum alloy wire in the titanium-aluminum composite material is an interface-modified Al-Si-Mg alloy wire, the Al-Si-Mg alloy wire in the interface-modified Al-Si-Mg alloy wire is one of 6061 aluminum alloy wire, 6063 aluminum alloy wire, and 6013 aluminum alloy wire.
4. The mobile phone frame based on titanium-aluminum composite material according to claim 1, characterized in that: The average particle size of the nano-scale interface modifier is 50-200nm; the nano-scale interface modifier includes a carrier and an over-plated metal element fixedly connected to the surface of the carrier in the form of a single atom through a covalent bond, the over-plated metal element is Ti and Al, and the mass ratio of Ti to Al is (0.8-1.2):(0.8-1.2); the carrier is at least one of MAX phase nano-ceramic powder, graphene, and carbon nanotubes; the MAX phase nano-ceramic powder is at least one of Ti2AlN nano-ceramic powder, Ti3AlC2 nano-ceramic powder, Ti3AlCN nano-ceramic powder, Ti2AlC nano-ceramic powder, and Al-Ti3AlC2 nano-ceramic powder; the doping rate of the over-plated metal element in the nano-scale interface modifier is 5-10wt%; The mass ratio of Ti and Al in the over-plated metal element is 1:1; the doping rate of the over-plated metal element in the nano-scale interface modifier is 8±0.5wt%; and the carrier is composed of carbon nanotubes and / or graphene combined with Al-Ti3AlC2 nano-ceramic powder.
5. The mobile phone frame based on titanium-aluminum composite material according to claim 4, characterized in that: The aluminum alloy wire in the titanium-aluminum composite material is an interface-modified Al-Si-Mg alloy wire, and the Al-Si-Mg alloy wire in the interface-modified Al-Si-Mg alloy wire is an aluminum alloy wire made of 6013--T4-S-ST-1-aluminum alloy; the interface-modified Al-Si-Mg alloy wire contains 0.5-0.8wt% of a nano-scale interface modifier, and the remainder is Al-Si-Mg alloy.
6. A processing technology for a mobile phone frame based on a titanium-aluminum composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Clean the wire surface: The cross section of the titanium wire material is a rectangle; the cross section of the aluminum alloy wire material is a right isosceles trapezoid; The titanium wire is ultrasonically cleaned by acetone, ultrasonically cleaned by deionized water, ultrasonically cleaned by acid solution, ultrasonically cleaned by deionized water, and low-temperature dried under nitrogen protection to obtain the titanium wire with a cleaned surface; At the same time, the aluminum alloy wire is ultrasonically cleaned with acetone, ultrasonically cleaned with deionized water, ultrasonically cleaned with acid solution, ultrasonically cleaned with deionized water, and low-temperature dried under nitrogen protection to obtain the aluminum alloy wire with surface cleaning treatment; Step 2: Wire surface roughening treatment: The titanium wire having the surface cleaned in step 1 is subjected to laser scanning roughening treatment, and then ultrasonically cleaned with acid solution, ultrasonically cleaned with deionized water, and low-temperature dried under nitrogen protection to obtain the titanium wire having the surface roughened; At the same time, the aluminum alloy wire having the surface cleaned in step 1 is subjected to laser scanning roughening treatment, and then ultrasonically cleaned with acid solution, ultrasonically cleaned with deionized water, and low-temperature dried under nitrogen protection to obtain the aluminum alloy wire having the surface roughened; Step 3, heating the wire at different temperatures: the titanium wire with surface roughening treatment in step 2 is subjected to high-frequency heating to 300-400°C for 100-120s, and then subjected to heat preservation treatment for 5-10min at 360-390°C; at the same time, the aluminum alloy wire with surface roughening treatment in step 2 is subjected to high-frequency heating to 400-460°C for 160-200s, and then subjected to heat preservation treatment for 5-10min at 400-440°C; the high-frequency heating temperature of the aluminum alloy wire is greater than the high-frequency heating temperature of the titanium wire; The cross section of the titanium wire obtained by the different-temperature heating treatment in step 3 is a rectangle, and the rectangular specification is a1*b1; in the rectangle, a1 is the length and b1 is the width; The cross section of the aluminum alloy wire obtained by the different temperature heating treatment in step 3 is a right isosceles trapezoid, and the rectangular specification is a2*b2*h; in the right isosceles trapezoid, a2 is the upper side length, b2 is the lower side length, and h is the height; b2 is 1.05-1.10 times of a2; a1 in the cross section of the titanium wire is smaller than b2 in the cross section of the aluminum alloy wire; Step 4, asynchronous rolling composite treatment: fix the aluminum alloy wire obtained by the step 3 temperature heating treatment on the top of the rolling mill, and fix the titanium wire obtained by the step 3 temperature heating treatment on the bottom of the rolling mill, the vertical bisector of the aluminum alloy wire along the length direction coincides with the vertical bisector of the titanium wire along the length direction, the upper surface area of the aluminum alloy wire is equal to the upper surface area of the titanium wire, the lower surface area of the aluminum alloy wire is equal to the upper surface area of the titanium wire, the lower surface of the aluminum alloy wire and the upper surface of the titanium wire are rolled and composited, that is, the connection interface of the aluminum alloy wire and the titanium wire, control the feed speed for asynchronous rolling, control the feed speed V1 of the aluminum alloy wire to 1.5-5m / min, control the feed speed V2 of the titanium wire to 3-10m / min, asynchronous rolling The cross section of the aluminum alloy wire before rolling is A1, the cross section of the aluminum alloy wire after asynchronous rolling is A1', the cross section of the titanium wire before asynchronous rolling is A2, the cross section of the titanium wire after asynchronous rolling is A2', the uniform discharge speed of the titanium-aluminum layered composite material is V, the aluminum alloy wire and the titanium wire feed satisfy the following formulas: A1×V1=A1'×V, A2×V2=A2'×V, the rolling mill is controlled to roll and composite the titanium wire and the aluminum alloy wire to form a rolling composite interface, during the rolling and composite process of the titanium wire and the aluminum alloy wire by the rolling mill, the titanium wire does not undergo plastic deformation, the rolling of the aluminum alloy wire undergoes plastic deformation, and a semi-finished titanium-aluminum layered composite material is obtained by rolling and composite, and the aluminum alloy wire in the obtained semi-finished titanium-aluminum layered composite material is plastically deformed and coated on the outer wall of the titanium wire; Step 5, double-sided edge grinding: sandpaper edge grinding is used to remove the aluminum alloy wire coated on the outer wall of the titanium wire, that is, sandpaper edge grinding is used to remove the aluminum alloy layer attached to the upper side wall, the lower side wall, and the lower bottom surface of the titanium wire; Step 6, cutting, edging, straightening and shaping: cutting and edging the titanium-aluminum layered composite material obtained by the double-sided edging treatment in step 5, grinding and chamfering the cutting edge, and then straightening and shaping to obtain a prefabricated titanium-aluminum layered composite material; Step 7: Solution treatment, aging treatment, and multi-point constant speed straightening treatment to obtain a finished titanium aluminum composite wire; Step eight, the finished titanium-aluminum composite wire is bent, welded end to end, and polished to form a titanium-aluminum alloy mobile phone frame.
7. The processing technology of a mobile phone frame based on titanium-aluminum composite material according to claim 6 is characterized in that: The roughness Ra of the surface-roughened titanium wire obtained in step 2 is 1-4 microns; the roughness Ra of the surface-roughened aluminum alloy wire obtained in step 2 is 2-5 microns; the roughness of the surface-roughened aluminum alloy wire obtained in step 2 is greater than the roughness of the surface-roughened titanium wire obtained in step 2; The step three is to perform different-temperature heating treatment on the wire: the titanium wire with surface roughening treatment in step two is subjected to high-frequency heating to 300-320°C for 120 seconds, and then subjected to heat preservation treatment for 10 minutes at 360-370°C; at the same time, the aluminum alloy wire with surface roughening treatment in step two is subjected to high-frequency heating to 400-420°C for 180 seconds, and then subjected to heat preservation treatment for 10 minutes at 400-420°C.
8. The processing technology of a mobile phone frame based on titanium-aluminum composite material according to claim 6 is characterized in that: The specific operation of step seven is as follows: the prefabricated titanium-aluminum layered composite material in step six is heated to 500-550°C within 10-18 minutes and kept warm for 20-40 minutes to complete the solid solution treatment, and then cooled to room temperature for 15-30 minutes in the furnace for aging treatment. The specific operation of the aging treatment is as follows: the prefabricated titanium-aluminum layered composite material is heated to 170-200°C within 5-10 minutes and kept warm for 3-5 hours, and then cooled to room temperature for 15-30 minutes in the furnace for multi-point constant speed straightening treatment to obtain the finished titanium-aluminum composite wire.
9. The processing technology of a mobile phone frame based on titanium-aluminum composite material according to claim 8 is characterized in that: The specific operation of step seven is as follows: the prefabricated titanium-aluminum layered composite material in step six is heated to 520°C within 15 minutes and kept warm for 30 minutes to complete the solid solution treatment, and then cooled to room temperature for 20 minutes in the furnace for aging treatment. The specific operation of aging treatment is: heated to 185°C within 5 minutes and kept warm for 4 hours, cooled to room temperature for 30 minutes in the furnace, and then multi-point constant speed straightening treatment is performed to obtain the finished titanium-aluminum composite wire.
10. The processing technology of a mobile phone frame based on titanium-aluminum composite material according to claim 6, characterized in that: In the asynchronous rolling and compounding process of step 4, during the rolling and compounding process of the titanium wire and the aluminum alloy wire by the rolling mill, the titanium wire does not undergo plastic deformation, and the rolling deformation of the aluminum alloy wire is 40-60%.
Citation Information
Patent Citations
Cast rolling device and method of titanium / aluminum alloy composite slab
CN106077554A
Preparation method of titanium-aluminum composite ultrathin plate with sandwich structure
CN113102503A